Measurement of CP violation parameters and polarisation fractions in B0s → J/ψK[bar]*0 decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
The first measurement of CP asymmetries in the decay $$ {B}_s^0\to J/\psi {\overline{\mathrm{K}}}^{\ast }{(892)}^0 $$and an updated measurement of its branching fraction and polarisation fractions are presented. The results are obtained using data corresponding to an integrated luminosity of 3.0 fb−1 of proton-proton collisions recorded with the LHCb detector at centre-of-mass energies of 7 and 8 TeV. Together with constraints from B0 → J/ψ ρ0, the results are used to constrain additional contributions due to penguin diagrams in the CP -violating phase ϕs, measured through Bs0decays to charmonium.
Im Titel ist die erste "0" hochgestellt, "S" ist tiefgestellt, "S" steht unter "0"
Im Titel ist der Buchstabe K mit einem Oberstrich dargestellt
Im Titel sind die zweite "0" und "*" hochgestellt
The LHCb Collaboration: R. Aaij, B. Adeva; M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, M. Britsch, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Schmelling, M. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, A. Zhelezov [und 689 weitere]
Gesehen am 07.04.2021